The association between population aging and oral and pharynx cancer incidence in the American continent (Colombia Medica, 2011)
Objective: The objective of this study was to explore the association between aging of population and incidence of oral cavity and pharynx cancer at the country level in the American continent. Methods: An ecological study at the country level. Countries’ data for oral cavity and pharynx cancer incidence comes from the International Agency for Cancer Research (GLOBOCAN 2002). Twenty eight countries were included from North America, Central America, and South America. The dependent variables were the countries’ oral cavity and pharynx cancer incidence rates (per 100,000/ year) by sex, overall and age-specific groups, 0-64 (younger population) and 65+ (older population), and the main independent variable was the countries’ aging population (% of persons 65 years and older). Other variables considered were per-capita gross national income and prevalence of smoking by sex at the country level. Results: Overall countries’ level of oral cavity and pharynx cancer incidence rates were strongly correlated with the countries’ aging population (p